1992
DOI: 10.1111/j.1432-1033.1992.tb17300.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel lactonohydrolase, catalyzing the hydrolysis of aldonate lactones and aromatic lactones, from Fusarium oxysporum

Abstract: A novel lactonohydrolase, an enzyme that catalyzes the hydrolysis of aldonate lactones to the corresponding aldonic acids, was purified 10-fold to apparent homogeneity, with a 61 % overall recovery, from Fusarium oxysporum AKU 3702, through a purification procedure comprising DEAESephacel, octyl-Sepharose CL-4B and hydroxyapatite chromatographies and crystallization. The molecular mass of the native enzyme, as estimated by high-performance gel-permeation chromatography, is 125 kDa, and the subunit molecular ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…Therefore, elucidation of the three-dimensional structure of the lactonohydrolase from F. oxysporum is important for the elucidation of the mechanisms underlying the stereoselectivity and substrate speci®city of the enzyme. The lactonohydrolase was easily crystallized by desalting (Shimizu et al, 1992), but the crystals obtained showed poor stability with respect to X-ray irradiation. In this study, we report the crystallization of the lactonohydrolase of F. oxysporum to give crystals suitable for atomic resolution X-ray structure analysis, and the preliminary crystallographic characterization of the lactonohydrolase.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, elucidation of the three-dimensional structure of the lactonohydrolase from F. oxysporum is important for the elucidation of the mechanisms underlying the stereoselectivity and substrate speci®city of the enzyme. The lactonohydrolase was easily crystallized by desalting (Shimizu et al, 1992), but the crystals obtained showed poor stability with respect to X-ray irradiation. In this study, we report the crystallization of the lactonohydrolase of F. oxysporum to give crystals suitable for atomic resolution X-ray structure analysis, and the preliminary crystallographic characterization of the lactonohydrolase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that Fusarium oxysporum produced a novel lactonohydrolase catalyzing the hydrolysis of aldonate lactones and aromatic lactones (Shimizu et al, 1992). The relative molecular mass of the native enzyme is 125 000, and the subunit molecular mass is 60 000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). specificity D-xylono--lactone (90%) L-pantoyl lactone and aromatic lactones but not for aldonolactones 10) synthetic lactones but not for aldonolactones 11) L--hydroxyglutaric acid--lactone 12) (R)-5-oxo-2-tetrahydrofran carboxylic acid and -butyrolactone 2,800 dihydrocumarin 9) 13.7 L-pantolactone 10) 230 (R)-5-oxo-2-tetrahydrofran carboxylic acid 11) 95 (S)-5-oxo-2-tetahydrofran carboxylic acid 11) 39.3 (S)-5-oxo-2-tetahydrofran carboxylic acid 3.6 D-galactonolactone 9) 6.3 dihydrocumarin 9) 3.59 L-pantoyl lactone 10) 1.9 (R)-5-oxo-2-tetrahydrofran carboxylic acid 11) 39.8 (S)-5-oxo-2-tetahydrofran carboxylic acid 11) 53 (S)-5-oxo-2-tetahydrofran carboxylic acid 12) EDTA/EGTA inhibited à inhibited 7,9,10) not inhibited 11,12) Restoration of lost Ca = Mg>Zn>Fe = Co, Ca, Mn, Zn 7) enzyme activity with Mn, Ni, Cu>Mo …”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] When D-glucose or D-glucose-6-phosphate is oxidized in cytoplasm by NAD(P)-dependent D-glucose dehydrogenase or NADP-dependent D-glucose-6-phosphate dehydrogenase, the corresponding lactone is formed and subsequently hydrolyzed to D-gluconic acid or 6-phospho-D-gluconic acid by the action of SGL.…”
mentioning
confidence: 99%